Visual-motor involvement in autism spectrum disorder: could the stereopsis deficit affect motor coordination? - Longo, Rosa; Allegrini, Francesca; Gusson, Elena; Morbio, Roberta; Di Gennaro, Gianfranco; Gozzi, Luigi Alberto; Marchini, Giorgio; Zoccante, Leonardo (Frontiers in Psychiatry, 2023)
Purpose: Given the known difficulty in sensory processing and in motor skills in patients with Autism Spectrum Disorder (ASD), and since visual impairment could interfere with children’s behaviour, early detection and management of visual-motor difficulties are crucial. This exploratory study aims to evaluate the visual-motor status in a cohort of children affected by ASD. Methods: The records of patients affected by ASD and admitted between 2018 and 2022 to the Pediatric University Hospital of Verona were reviewed. Best Corrected Visual Acuity, cycloplegic refraction, stereopsis, convergence, complete ocular motility, strabismus examination, slit-lamp anterior segment examination and fundus ophthalmoscopy were collected and reviewed. Results: A total of 253 patients (203 ASD and 50 healthy controls) were included in the study. A higher number of total orthoptic defects were detected in the ASD group, in comparison with the control group. Specifically, a higher percentage of stereopsis deficit and convergence insufficiency was observed. Conclusion: In our cohort of children with ASD stereopsis deficit, convergence insufficiency and refractive errors are the most observed ocular conditions. These findings are consistent with the known alterations of motor skills and sensory processing in ASD. Moreover, our study supports the hypothesis that visual acuity is not compromised in children with ASD. As a result, a complete ophthalmic evaluation is highly recommended in children with ASD, to guarantee early detection and treatment of possible visual-motor defects.